Noise Mapping of the Flyover Highway in Genoa: comparison of different methods - Borelli Davide; Repetto Simona; Schenone Corrado (Noise Mapping, 2014)
In urban noise mapping the accuracy of the simulation tools is often challenged by the complexity of the modeled scenario, particularly when its extent coincide with the whole city. In this paper, a meaningful case study is reported concerning the flyover highway “Aldo Moro” in Genoa. The particular morphology of the city and the location of the highway make it a significant test for analyzing the effectiveness of current modeling tools in simulating complex urban areas. Noise mapping has been implemented in accordance with the standardNMPB-Routes- 2008. Results have been then analyzed complying with the END. Next diverse computational methods have been compared, considering ISO 9613-2, NMPB-Routes-1996, and Harmonoise, and even different frequency partitions (octave band or one-third octave band) for the last two standards. The computational time for the different calculation methods has been analyzed. In order to get a reciprocal validation, the simulated noise maps have been finally compared with maps coming from on field measurements. In this way a case study helpful for public administrations and stakeholders facing similar issues is provided, defining the state of the art and the forthcoming perspectives.